PENERAPAN MODEL PREDICT OBSERVE EXPLAIN BERBANTUAN MEDIA SCRAPBOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD - Linda Ayu Kusumaningsih; Fina Fakhriyah; Mila Roysa (PROGRES PENDIDIKAN, 2020)
This study aims to describe the increase in critical thinking skills using the predict observe explain learning model assisted by scrapbook media in class V SD 1 Jepang Kudus. This type of research is classroom action research. This type of research is classroom action research. This research consists of 4 stages namely planning, action, observation, and reflection. The research was conducted in 2 cycles with 2 meetings each cycle. The subjects of this study were 27 students of grade V SD 1 Jepang Kudus in the 2019/2020 school year. The results showed that students' critical thinking skills in cycle 1 obtained classical completeness by 63% with the criteria needed guidance, while in cycle 2 they obtained classical completeness by 85% with good criteria.